(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
This article summarizes the maim approaches to teacher training experience of academics in the Universidad National Experimental de Guayana (UNEG), with the aim of spreading their progress and contribute to the debate on this issue that in the country is generated. It is divided in to five sections: The first refer to the antecedent, politics and regulations of the UNEG related to de the process of academic formations; The second mentioned preliminary results of the institutional research project: "Facts, Beliefs and Expectation, about the academic UNEG formations", which have contributed to its operationalization The third details the training model: its psychological principles, educational and as well as educational and organizational, core component and process map. The fourth part describes The Integrated Systems of Academic Chase as a support systems form the delivery of training. Finally, in part five reflects some conclusions and the actual situation of the UNEG. The methodological processes inherent to the model come from documental review of others university and those that the UNEG have. Among the findings highlight the benefits that virtual supports have to advance the implementation of the first model designed for teachers in the seven places where the UNEG is located, also the relevance of the principles that govern it and the undertake a deeper educational process on the model, for those with responsibility to its implementation.